2021
DOI: 10.3389/frwa.2021.725174
|View full text |Cite
|
Sign up to set email alerts
|

The Impacts of Climate Change and Porous Pavements on Combined Sewer Overflows: A Case Study of the City of Buffalo, New York, USA

Abstract: Combined sewer overflows (CSOs) release pollutants collected in urban runoff into local waterways, impacting both aquatic life and human health. The impact of climate change on precipitation may result in an increase in the frequency and magnitude of heavy precipitation events, with a corresponding increase in CSO discharges. The installation of Green Infrastructure (GI) such as Porous Pavements (PP) is a resilient approach to mitigate CSO events. However, an understanding of the impact of climate change on CS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…SuDS are a complement to conventional sewer system infrastructure to minimize the hydrological impacts of urbanization and increase resilience to climate change in urban areas [ 41 ]. These measures are intended to limit extreme precipitation events [ 40 ] and are known to provide many environmental benefits [ 42 ], including the mitigation of climate change impact [ 43 , 44 , 45 , 46 ], along with ecological and social benefits and other potential long-term economically quantifiable benefits [ 47 , 48 , 49 ]. Types of SuDS include green roofs, permeable surfaces, wetlands, detention and infiltration basins, and filter drains, among others [ 50 ].…”
Section: Urban Practices To Mitigate Soil Sealing: Typologies Charact...mentioning
confidence: 99%
“…SuDS are a complement to conventional sewer system infrastructure to minimize the hydrological impacts of urbanization and increase resilience to climate change in urban areas [ 41 ]. These measures are intended to limit extreme precipitation events [ 40 ] and are known to provide many environmental benefits [ 42 ], including the mitigation of climate change impact [ 43 , 44 , 45 , 46 ], along with ecological and social benefits and other potential long-term economically quantifiable benefits [ 47 , 48 , 49 ]. Types of SuDS include green roofs, permeable surfaces, wetlands, detention and infiltration basins, and filter drains, among others [ 50 ].…”
Section: Urban Practices To Mitigate Soil Sealing: Typologies Charact...mentioning
confidence: 99%
“…In some areas the increase of high intensity rain events will result in more frequent wet-weather discharges. 10,11 Tavakol-Davani et al 12 estimated an increase in wet-weather discharge frequency (18%), volume (12%), and duration (17%) in Toledo (Ohio, USA). Salerno et al 13 estimated an increase of 40% in phosphorus load in a river in northern Italy.…”
Section: Introductionmentioning
confidence: 99%
“…Managing and reducing these discharges from combined sewer overflows (CSOs) has become a priority of public policies and water utilities worldwide, due to increased attention towards water quality (European Commission, 2000;UK Government, 2021;United Nations, 2018). In the face of emerging pressures such as climate change and urbanisation, the issues associated with CSOs are likely to increase (e.g., water quality and ecological impacts on receiving waters) (Astaraie-Imani et al, 2012;IPCC, 2022;Roseboro et al, 2021). Therefore, there is agreement that CSS need to be redesigned to support resilience (Butler et al, 2017;Marlow et al, 2013;Ofwat, 2015; UNESCO World Water Assessment Programme, 2018;) -i.e., the ability to minimise failure magnitude and duration under exceptional conditions (Butler et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Among the different interventions in CSS to enhance resilience, decentralised stormwater strategies that mimic natural processes, such as "green infrastructure" (GI) (e.g., green roofs, bioretention cells, permeable pavements) (Browder et al, 2019;Fletcher et al, 2015;Matsler et al, 2021), are gaining popularity. Research has demonstrated the efficacy of GI under various precipitation conditions, with some studies showing significant reductions in CSO volume (24-100% reduction) through the implementation of different GI types under different spatial allocations (Casal-Campos et al, 2015Joshi et al, 2021;Lucas and Sample, 2015;McClymont et al, 2020;Rodriguez et al, 2021;Roseboro et al, 2021). Conflicting findings on the effectiveness of GI in reducing CSOs suggest a need for further exploration of GI's relationship with CSS resilience performance, as current literature lacks clear characterisation in this regard.…”
Section: Introductionmentioning
confidence: 99%